THE ROLE OF ENVIRONMENTAL PERFORMANCE TO REALIZE GREEN ECONOMY DEVELOPMENT EFFECT ON MINING COMPANIES' FINANCIAL PERFORMANCE - Evelyn Wijaya; Teddy Chandra; Layla Hafni; Martha Ng; Suharti (Universitas Tidar, 2022)
This study aimed to analyze the effect of environmental costs on the company's financial performance with environmental performance as an intervening variable. The data used were secondary data. The number of mining companies that became the research sample were 20 companies out of a total of 49 companies listed on the Indonesia Stock Exchange. The data analysis technique used was path analysis with using the SEM-AMOS program. The results of the study show that environmental costs have no significant effect on environmental performance and company financial performance. Also, environmental performance has no significant effect on the company's financial performance. Furthermore, the results of the study show that environmental performance has not been able to mediate the effect between environmental costs and financial performance